2016
DOI: 10.1016/j.aorn.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcers: Factors Contributing to Their Development in the OR

Abstract: The prevention of health care-associated pressure ulcers (HAPUs) is an important quality measure because HAPUs are considered a never event. The literature suggests that the prevalence rate of pressure ulcers is 8.5% or higher among patients who undergo surgical procedures that last longer than three hours. We performed a retrospective chart review to determine what factors contribute to the development of pressure ulcers in patients who undergo surgical procedures. The sample population included patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
19

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 21 publications
4
85
0
19
Order By: Relevance
“…Patients scoring below 16 on the Braden Scale are considered at risk. One study determined that the risk of pressure injury occurrence increased 58% with each decreasing unit on the Braden Scale . Approximately 25% of our patients are found to be at risk of pressure injury before undergoing an operative or other invasive procedure.…”
Section: Perioperative Pressure Injury Prevention Programmentioning
confidence: 89%
See 2 more Smart Citations
“…Patients scoring below 16 on the Braden Scale are considered at risk. One study determined that the risk of pressure injury occurrence increased 58% with each decreasing unit on the Braden Scale . Approximately 25% of our patients are found to be at risk of pressure injury before undergoing an operative or other invasive procedure.…”
Section: Perioperative Pressure Injury Prevention Programmentioning
confidence: 89%
“…All perioperative patients are at risk for pressure injury because they are immobile during the procedure; unable to feel pain caused by pressure, friction, or shear forces; and unable to change position to relieve the pressure on a particular area . Studies correlating the length of the operative or other invasive procedure and pressure injury development are inconclusive . A recent study focusing on sacral pressure injuries in critically ill surgical patients found that a shorter procedure duration increased the risk of pressure injuries .…”
Section: Surgical Patients and Pressure Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the patient characteristics and procedures in acute care (eg emergency admissions, trauma and critically ill patients, unstable health conditions), PU risk is high in these particular hospital patient groups . Patient transfer, surgical procedures, and the involvement of many disciplines and professions have especially been identified as typical environmental PU risk factors in hospitals . At the same time, PU risk may still be under‐detected .…”
Section: Discussionmentioning
confidence: 99%
“…Extreme changes in body mass index (BMI), as in patients classified as lean or obese, are considered to be predisposing factors for the occurrence of ulcers. Obesity may enhance the complications resulting from positioning, and low weight results in the increased exposure of the patient's bony prominences, leaving the regions more susceptible to PUs (Association of periOperative Registered Nurses [AORN], ; Engels et al, ).…”
Section: Introductionmentioning
confidence: 99%